Plastic voided slab systems: applications and design - Midkiff, Corey J. (Kansas State University, 2013)
Reinforced concrete slabs are one of the most common components in modern building construction. Reinforced concrete slabs with plastic voids slabs are a new and innovative type of structural, concrete slab system developed to allow for lighter self-weight of the structure while maintaining similar load carrying capacity of a solid slab. Plastic voided slabs are capable of reducing the amount of concrete necessary to construct a building by 30 percent or more. This reduction can be beneficial in terms of financial savings as well as building performance. This report examines a two-way, reinforced concrete slab with plastic voids construction in comparison to traditional flat plate reinforced concrete slab construction. The design process for plastic voided slabs is directly compared with traditional two-way flat plate reinforced concrete slabs through a design comparison of typical bays of 20’ by 20’ (6m by 6m), 25’ by 25’ (7.6m by 7.6m), 30’ by 30’ (9m by 9m) and 35’ by 35’ (10.7m by 10.7m). The traditional slab design process follows the ACI 318-11 Building Code Requirements for Structural Concrete chapter 13 Direct Design Method, while the plastic voided slab design process is modified from the BubbleDeck Design Guide for compliance with BCA using AS3600 and EC2. Sizes of traditional slab bays are compared to sizes of plastic voided slab bays. Results of the comparison study are presented.
Keywords: Plastic Voided Slab; Concrete; Slab; BubbleDeck; Cobiax; Architectural engineering (0462); Architecture (0729); Civil Engineering (0543)